Compartmentalization of phosphatidylinositol 4,5-bisphosphate metabolism into plasma membrane liquid-ordered/raft domains - Myeong, Jongyun (Proc Natl Acad Sci U S A, 2021)
Possible segregation of plasma membrane (PM) phosphoinositide metabolism in membrane lipid domains is not fully understood. We exploited two differently lipidated peptide sequences, L10 and S15, to mark liquid-ordered, cholesterol-rich (L(o)) and liquid-disordered, cholesterol-poor (L(d)) domains of the PM, often called raft and nonraft domains, respectively. Imaging of the fluorescent labels verified that L10 segregated into cholesterol-rich L(o) phases of cooled giant plasma-membrane vesicles (GPMVs), whereas S15 and the dye FAST DiI cosegregated into cholesterol-poor L(d) phases. The fluorescent protein markers were used as Förster resonance energy transfer (FRET) pairs in intact cells. An increase of homologous FRET between L10 probes showed that depleting membrane cholesterol shrank L(o) domains and enlarged L(d) domains, whereas a decrease of L10 FRET showed that adding more cholesterol enlarged L(o) and shrank L(d). Heterologous FRET signals between the lipid domain probes and phosphoinositide marker proteins suggested that phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P(2)] and phosphatidylinositol 4-phosphate (PtdIns4P) are present in both L(o) and L(d) domains. In kinetic analysis, muscarinic-receptor-activated phospholipase C (PLC) depleted PtdIns(4,5)P(2) and PtdIns4P more rapidly and produced diacylglycerol (DAG) more rapidly in L(o) than in L(d). Further, PtdIns(4,5)P(2) was restored more rapidly in L(o) than in L(d). Thus destruction and restoration of PtdIns(4,5)P(2) are faster in L(o) than in L(d). This suggests that L(o) is enriched with both the receptor G protein/PLC pathway and the PtdIns/PI4-kinase/PtdIns4P pathway. The significant kinetic differences of lipid depletion and restoration also mean that exchange of lipids between these domains is much slower than free diffusion predicts.